Deleuze, Balthasar, and John Paul II on the Aesthetics of the Body - Franks, Angela (Theological studies, 2020)
Is the body a grid or a window? For Gilles Deleuze, as for most post-structuralists, the body does not express the person but rather functions as a surface upon which desire writes. Deleuze’s aesthetics of the surface echoes the inchoate convictions of transgenderism. In contrast, for classical Christian aesthetics, the beauty of the surface is an expression of depth. Hans Urs von Balthasar’s theological aesthetics is analyzed along John Paul II’s theology of the body, in which the body expresses the person. I close with a trinitarian analogy of the body.